Assessing climate change mitigation proposals for Malaysia: Implications for emissions and abatement costs - Rasiah R.; Al-Amin A.Q.; Mintz Habib N.; Chowdhury A.H.; Ramu S.C.; Ahmed F.; Filho W.L. (Elsevier Ltd, 2023)
Environmental regulations; Global warming; Carbon pricing; Climate change mitigation; INDC; Malaysia; UNFCCC; Costs